The Role of Gut and Airway Microbiota in Pulmonary Arterial Hypertension - Huang, Linlin; Zhang, Hongdie; Liu, Yijun; Long, Yang (Frontiers in Microbiology, 2022)
Pulmonary arterial hypertension (PAH) is a severe clinical condition characterized pathologically by perivascular inflammation and pulmonary vascular remodeling that ultimately leads to right heart failure. However, current treatments focus on controlling vasoconstriction and have little effect on pulmonary vascular remodeling. Better therapies of PAH require a better understanding of its pathogenesis. With advances in sequencing technology, researchers have begun to focus on the role of the human microbiota in disease. Recent studies have shown that the gut and airway microbiota and their metabolites play an important role in the pathogenesis of PAH. In this review, we summarize the current literature on the relationship between the gut and airway microbiota and PAH. We further discuss the key crosstalk between the gut microbiota and the lung associated with PAH, and the potential link between the gut and airway microbiota in the pathogenesis of PAH. In addition, we discuss the potential of using the microbiota as a new target for PAH therapy.